2022
DOI: 10.1016/j.pathol.2021.06.124
|View full text |Cite
|
Sign up to set email alerts
|

Progression of mesothelioma in situ to invasive disease 4 years and 10 months after initial diagnosis

Abstract: Progression of mesothelioma in situ to invasive disease 4 years and 10 months after initial diagnosis CORRESPONDENCE Pathology (xxxx), xxx(xxx), -Please cite this article as: Klebe S, Progression of mesothelioma in situ to invasive disease 4 years and 10 months after initial diagnosis, Pathology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Recently, whole-exome sequencing confirmed that mesothelioma in situ development is associated with BAP1 somatic mutations/deletions, suggesting that BAP1 mutations/deletions represent a very early event in the development of malignant mesothelioma ( 3 ). Recently, new diagnostic tools, such as radiogenomics, have helped identify the potential correlation between imaging findings and tumour genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, whole-exome sequencing confirmed that mesothelioma in situ development is associated with BAP1 somatic mutations/deletions, suggesting that BAP1 mutations/deletions represent a very early event in the development of malignant mesothelioma ( 3 ). Recently, new diagnostic tools, such as radiogenomics, have helped identify the potential correlation between imaging findings and tumour genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Cases with shorter latency have been reported, and there may be cases with earlier and shorter asbestos exposures that have not been recognised because of the lack of an accurate assessment of asbestos exposure. Referring to short latency, mesothelioma is now diagnosed earlier via cytology, and non-invasive forms have been identified, such as in situ mesothelioma, which may affect the possibility of early diagnosis ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have presented a case of MIS that showed obviously malignant mesothelial cells based on cytology of pleural effusion. Based on our search of the literature, 17 cases of pleural MIS have been reported (Table I) (2,(5)(6)(7)(8)(9)(10)(11)(12). According to available data from previous reports, MIS was confirmed only in 8 cases before progression to mesothelioma (2,5,6,8,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our search of the literature, 17 cases of pleural MIS have been reported (Table I) (2,(5)(6)(7)(8)(9)(10)(11)(12). According to available data from previous reports, MIS was confirmed only in 8 cases before progression to mesothelioma (2,5,6,8,10,11). It is difficult to suspect MIS at the time of sampling due to unremarkable clinical findings including symptoms, serum tumor markers, radiology, and even pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Then, two cases of mesothelial lesions characterized by only surface cells and no invasion (or minute invasive foci) but harboring the aforementioned molecular abnormalities were suggested as being true mesothelioma in situ cases [87]. Similarly, another case of proposed mesothelioma in situ [89] progressed to invasive disease almost five years later [90]. Following their initial observation, a group of experts in mesothelial pathology gathered another nine cases diagnosed with the following strict criteria: single layer of surface mesothelial cells with lost BAP1 expression, no evidence of invasive tumor by imaging techniques or during visual inspection of the serosal cavity, and no invasive mesothelioma diagnosed for at least 12 months after initial biopsy to avoid initial misdiagnoses [91].…”
Section: Non-specific Pleuritismentioning
confidence: 99%